Environmental Education in Environmental Engineering: Analysis of the Situation in Colombia and Latin America - Acosta Castellanos, Pedro Mauricio; Queiruga-Dios, Araceli; Hernández Encinas, Ascensión; Acosta, Libia Cristina (Sustainability, 2020)
Environmental education (EE) has become the only tool for environmental sustainability in training processes in Colombia, for basic cycles in primary and secondary, as well as university education. EE tends to transform human actions in nature, based on multidisciplinary knowledge that supports decision-making. Its goal is to generate a change in social behavior in order to achieve the recovery, conservation, and preservation of the environment. In Colombia, education for sustainable development (ESD) is embedded in EE. These educational models (EE and ESD) seek to achieve sustainable development goals (SDGs), which generally seek the economic and social well-being of nations, both for current and future generations. Environmental engineering is a relatively new degree course in Colombia and Latin America since it appeared in the mid-nineties, and it must involve EE within its curriculum. Students are trained in this trend. This research intends to demonstrate, through a curricular review of the environmental engineering curricula and also surveying students from this degree, the level of inclusion of EE in Latin America. Strengths are identified in the curricula, such as the strong presence of EE in disciplinary subjects and opportunities for improvement based on the needs of the students. The situation in South America is also included in this study.